Pesticide degradation on solid surfaces: a moisture dependent process governed by the interaction between TiO2 and H2O - Yang Wenda; Wang Zhongwen; Bin Yang; Jiang Yu; Sun Meizhou; Liu Xinghuan; Amin Babar; Ge Guixian; Rodriguez (Rodriges) Contreras R. D. Raul David; Jia Xin (2021, 2021)
Title screen